Comparative morphology of adult Lernaea polymorpha Yu and Lernaea cyprinacea Linnaeus. - Sharif, M.; C., Sommerville (1989)
The comparative morphology of Lernaea ctprinacea (Asian type) from Aristichtys nobilis and Carassius auratus and of L.polymorpha from A.nobilis was studied. The morphological variations of adult parasites from different regions of each host was also determined. Three forms of Lernaea were produced from C.auratus infected with L.cyprinacea (Asian type), L.cyprinacea identical to the maternal form, L.cyprinacea (Europen type)and Lernaea ctenopharyngodonis in the proportion of 24.5, t.2 and 68.3%, respectively. Lernaea ctenopharyngodonis was thus confirmed to be a synonym of L.cyprinacea. Only one form of Lernaea was identified from A.nobilis, L. cyprinacea identical to the maternal form. Infection of L.polymorpha on A.nobilis produced adult identical to its maternal form. A high number of abnormal forms of L.cyprinacea were contained from the head, fins and caudal peduncle. In C.auratus it was 36%. Infection of L.polymorpha in A.nobilis revealed 21% abnormanl forms from the caudal peduncle,head and fins.